The Influence of Organizational Learning And Work Motivation on Job Satisfaction And Its Implications on Employee Performance - Indah Budi Hastuti; Stevani Kurnia Avisah; Hendri Herman (Citakonsultindo, 2023)
The purpose of this research is to know and analyze: (1) Organizational Learning; (2) Work Motivation; (3) Job Satisfaction, (4) Employee Performance and (5) The Influence of Organizational Learning and Work Motivation on Job Satisfaction and the Implications for Employee Performance in Food and Beverage Companies in South Jakarta City.The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study was the employees of the Food and Beverage Company in South Jakarta, with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional.Based on the results of the study, it was found that the Organizational Learning of Employees in Food and Beverage Companies in South Jakarta City was generally good and Employee Work Motivation in Food and Beverage Companies in South Jakarta City was generally good, Employee Job Satisfaction in Food and Beverage Companies in South Jakarta City is currently assessed good and Job Satisfaction effect on Employee Performance. Organizational Learning and Work Motivation affect Employee Job Satisfaction in Food and Beverage Companies in South Jakarta City. Organizational Learning and Work Motivation affect Employee Performance in Food and Beverage Companies in South Jakarta City. Employee Job Satisfaction on Employee Performance in Food and Beverage Companies in South Jakarta City.Work Motivation influences Job Satisfaction dominantly, so Food and Beverage Companies in South Jakarta City must maintain this condition so that Job Satisfaction for employees in the Food and Beverage Company Environment in South Jakarta City remains consistent.